2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152351
|View full text |Cite
|
Sign up to set email alerts
|

Robust hitting with dynamics shaping

Abstract: The present paper proposes the motion planning based on "the dynamics shaping" for a robotic arm to hit the target robustly toward the desired direction, of which the concept is to shape the robot dynamics appropriately in order to accomplish the desired motion. According to the linear system theory, the positional error of the end-point converges onto near the singular vector corresponding to its maximum singular value of the output controllability matrix of the robotic arm. Therefore, if we can control the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is found that the manipulation task accuracy depends on the grasp configuration such as the contact position, the hand configuration and the object's position and orientation. We propose a novel grasp planning which finds the grasp configuration with high manipulation task accuracy, which is called "dynamics shaping" [12]. As a simulation example, Fig.…”
Section: Grasp Planning Based On Dynamics Shapingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the manipulation task accuracy depends on the grasp configuration such as the contact position, the hand configuration and the object's position and orientation. We propose a novel grasp planning which finds the grasp configuration with high manipulation task accuracy, which is called "dynamics shaping" [12]. As a simulation example, Fig.…”
Section: Grasp Planning Based On Dynamics Shapingmentioning
confidence: 99%
“…The dynamics shaping has been applied to plan the robot arm's global motion such as the hitting motion [12] and the tracking motion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Changing arm postures to obtain arm's dynamics and kinematics which are insusceptible to unknown disturbances is called dynamics shaping [10]. We consider that errors perpendicular to the direction of a desired end-effector's motion are more important in tracking tasks such as welding and painting since such errors cause collision with a workpiece.…”
Section: Application To Motion Planningmentioning
confidence: 99%
“…However, these methods have not designed to find arm motions which are insusceptible to unknown disturbances. In this paper, based on our previous work on robust hitting by the robotic arm [10], [11], which finds the arm trajectory insusceptible to unknown disturbances for hitting a stationary object, a novel tracking motion planning method is proposed. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%